Surface packing characterization of Langmuir monolayer-anchored enzyme - Narayanan, Ravindrabharathi (Langmuir : the ACS journal of surfaces and colloids, 2009)
We have synthesized a novel interface-anchoring alcohol dehydrogenase by covalent attachment of a hydrophobic polymer tail to the hydrophilic protein head. Analogous to a protein-based surfactant, this polymer-enzyme conjugate self-assembled at liquid-liquid or liquid-air interfaces to form a membrane similar to other surfactant monolayers. The packing and morphology of the interface-anchored enzymes play an important role in regulating the membrane behaviors including enzyme mobility and interfacial interactions of enzymes with reactant and product molecules. To characterize the surface assembly morphology of the interface-anchored enzymes, Langmuir film balance and fluorescence microscopy techniques were used. The Langmuir isotherm of the interface-anchored enzyme demonstrated a pronounced molecular rearrangement upon compression of the isotherm. This corresponded to changes in membrane morphology and state observed using fluorescence microscopy. The molecular diffusion within the novel interface-anchored enzymes was further evaluated by using a fluorescence recovery after photobleaching technique. We report a diffusion coefficient of 6.7x10(-10) cm2/s. The study represents the first in-depth analysis of surface packing and interfacial mobility of such interface-anchored enzymes